Noisy signals: Do ratings' volatility depend on the length of the consumption span? - David Boto-García; Veronica Leoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
This paper investigates the informational content of online reviews. For the case of hotels, we model how the length of the stay shapes the variance of review scores. Grounded on violations of temporal monotonicity, errors in recall and hedonic adaptation theories, we first present a characterization of how the consumption span affects the non-deterministic component of consumer satisfaction. Next, we conduct an empirical analysis using more than 525,000 individual reviews from Booking.com in 5 major European cities. Under a heteroskedastic framework, we document that individual ratings' volatility decreases with the length of the stay. This implies that online ratings from short stayers (short consumption episodes) are noisy signals of the underlying hotel quality. Furthermore, we show that greater volatility in hotel ratings translates into a lower share of useful reviews for subsequent consumers. Our findings offer relevant insights for platform design operators about the sources of ratings' volatility and how this affects social learning.
Keywords: D12; D83; Z30; 330; online reviews; ratings' variance; length of stay; quality uncertainty; heteroskedasticity; Booking.com